Quality Reliability Service Towards Student Satisfaction - Isnaeni, Fajar; Widagdo, Suwignyo; Supardi, Supardi (Universitas Pendidikan Ganesha, 2019)
This study aims to examine and analyze the simultaneous effect of service quality on student satisfaction, test and analyze the partial effect of service quality on student satisfaction, test and analyze variables that have a dominant influence on student satisfaction. This research method uses multiple linear regression analysis which is used to determine how much influence the independent (independent) variables, namely Tangible, Reliability, Responsiveness, Assurance, Empathy on the dependent variable is student satisfaction. Research site is at STES Ihya 'Ulumiddin Banyuwangi. The study took a sample of 39 people. While the results of this study can be drawn as follows, the variables Tangible, Reliability, Responsiveness, Assurance and Emphaty simultaneously affect student satisfaction. The partial test of the Reliability variable, Responsiveness, Assurance and Emphaty is positive, but the Tangible variable is negative. Reliability variables are variables that have a dominant and significant influence on student satisfaction.